Factors associated with non-essential workplace attendance during the COVID-19 pandemic in the UK in early 2021: evidence from cross-sectional surveys. (September 2021) - Michie, S.; Potts, H.W.W.; West, R.; Amlȏt, R.; Smith, L.E.; Fear, N.T.; Rubin, G.J.
Abstract: Objectives: Working from home where possible is important in reducing the spread of COVID-19. In early 2021, a quarter of people in England who believed they could work entirely from home reported attending their workplace. To inform interventions to reduce this, this study examined associated factors. Study design: Data from the ongoing COVID-19 Rapid Survey of Adherence to Interventions and Responses survey series of nationally representative samples of people in the UK aged 16+ years in January–February 2021 were used. Methods: The study sample was 1422 respondents who reported that they could work completely from home. The outcome measure was self-reported workplace attendance at least once during the preceding week. Factors of interest were analysed in three blocks: 1) sociodemographic variables, 2) variables relating to respondents' circumstances and 3) psychological variables. Results: 26.8% (95% confidence interval [CI] = 24.5%–29.1%) of respondents reported having attended their workplace at least once in the preceding week. Sociodemographic variables and living circumstances significantly independently predicted non-essential workplace attendance: male gender (odds ratio [OR] = 1.85, 95% CI = 1.33–2.58); dependent children in the household (OR = 1.65, 95% CI = 1.17–2.32); financial hardship (OR = 1.14, 95% CI = 1.08–1.21); lower socio-economic grade (C2DE; OR = 1.65, 95% CI = 1.19–2.53); working in sectors such as health or social care (OR = 4.18, 95% CI = 2.56–6.81), education and childcare (OR = 2.45, 95% CI = 1.45–4.14) and key public service (OR = 3.78, 95% CI = 1.83–7.81) and having been vaccinated (OR = 2.08, 95% CI = 1.33–3.24). Conclusions: Non-essential workplace attendance in the UK in early 2021 during the COVID-19 pandemic was significantly independently associated with a range of sociodemographic variables and personal circumstances. Having been vaccinated, financial hardship, socio-economic grade C2DE, having a dependent child at home and working in certain key sectors were associated with higher likelihood of workplace attendance.